Kalam and its relevance in Muslim scholarship of religion: an integrated approach - Ibrahim, Haslina (IIUM Press, 2023)
The work addresses a methodological dilemma faced by Muslim learners of Comparative Religion, a modern approach in the study of religions. They were demanded to detach from their faith when studying religions other than Islam. In other words, they have to be neutral. This is called suspension of judgment. It is to prevent them from being judgmental towards other religious truths. On the other hand, the traditional methods introduced by scholars of Kalam were critical of other religions. They made it mandatory to decipher religious truth from error as they were all out in defence of the creeds of Islam from false allegations and rectifying the flaws of other religions. Such, in the view of modern scholars of religions, is exclusive, prejudicial, biased, and non-objective. This book therefore attempts to resolve such a methodological dilemma. It offers meaningful intellectual engagement via an integrated approach by recognising the Kalam methods and the modern methods as they are both indispensable in the contemporary study of religions.